Mimetic Reading of J.K. Rowling’s The Casual Vacancy: A Political Critique of the United Kingdom’s 2010 General Election Through the Analysis of Children Characters’ Sufferings - Levina Elsa Prastiwi Sugiyanto; Moh. Arif Rohman (Lexicon, 2023)
In 2010, the United Kingdom called on a General Election after the Queen agreed to grant an approval to Gordon Brown’s proposal to dissolve the parliament. The Queen’s approval resulted on prorogation marking the end of Gordon Brown’s parliamentary period. The General Election was used as a stage for the United Kingdom’s three biggest parties to assert their political dominance. Publishing her first novel for adult, The Casual Vacancy, J.K. Rowling attempted to deliberate the change of political atmosphere during the major event.The recent paper employs Paul Ricoeur’s Threefold Mimesis to analyse the symbolisms presented in The Casual Vacancy in order to demonstrate how it is used as a means of constructive criticism of the three biggest parties participating in the UK’s 2010 General Election. The criticism mentioned in this paper are based on writer’s interpretation. Those are the Conservative needs to evaluate its rigid, too right-winged, outdated policies and to expunge its tendency of establishing class-exclusivity, Labour Party needs to evaluate its members and to pay more attention to its supporters’ concerns; Liberal-Democrats needs to resolve its scandals and to be more selective in postulating its candidates. Details are discussed.